(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Security is one of the major concerns in our societies today, and the issues related to it are steadily increasing in both intensity and complication. Predicting crimes could help, but that is a huge challenge as it requires a study of the behavioral pattern or trend of criminal activities. This research aims to develop an Intelligent Crime Management System for the Nigeria Police Force using a case study of Lafia metropolis in Nasarawa State. The java development kit (JDK), android software development kit (SDK), sinch sdk for app-to-app call, android studio, firebase and a virtual emulator, were used to accomplish the research objectives. This system is comprised of an android based mobile application for crime reporting and awareness, a geospatial database that houses both legacy and new crime data, and a web-based intelligent application. The system can utilize the crime data stored in the database to identify hotspots and clusters in the Lafia metropolis. It can also predict the crime likely to occur at a location and analyze risk assessment and situation assessment of crime in Lafia metropolis